A emergência dos processos primários no TAT da Escola de Paris em adultos com diagnóstico de esquizofrenia - Álvaro José Lelé (2013)
The present study aims to investigate the primary processes of thoughts and how these are expressed in the Thematic Apperception Test (TAT). The TAT is a significant projective instrument used to make assessments of psychological functioning since the 1930s. It was developed by Henry Murray and Christiana Morgan. The primary process is an essential concept in the psychoanalytic theories as regards the unconscious aspects of psychic functioning. Its main characteristics are the absence of coherence and logical relations, the lack of knowledge of temporal relations and of the reality principle. This way of functioning is characteristic and most often seen in schizophrenic individuals. The TAT allows for different types of assessments and is recognized as an efficient tool in identifying these processes. In the present study, the results were analyzed according to the Parisian School. Specifically, the emergences of the primary processes by utilizing the TAT with schizophrenic adults were analyzed. 32 individuals, aged 24 to 60, of both genders, have taken part in the present study and have been divided into two groups of 16 each: a clinical group diagnosed as schizophrenic patients by medical teams, and a non-clinical group. The TAT was administered individually, during a single session. The study focused on the procedures of the Series A, B, C and E of the Test Scoring Sheet, adopted by the Parisian School. The means obtained from both groups were compared using a non-parametric technique called Mann-Whitney and then, discriminant analysis was estimated. The results showed statistically significant differences between the groups in the E Series. In addition, eight sub-criterions from E Series correctly classified 90% of sample. It has been concluded that the E Series of TAT constitutes a valid indicative of differentiation between the clinical group comprised of patients diagnosed with schizophrenia, and the non-clinical groups, comprised of individuals outside this pathology.